Performance on the ROCF at 8 Years Predicts Academic Achievement at 16 Years in Individuals with Dextro-Transposition of the Great Arteries. (14th October 2021) - Fasano-McCarron, Matthew E.; Bernstein, Jane Holmes; Waber, Deborah P.; Newburger, Jane W.; DeMaso, David R.; Bellinger, David C.; Cassidy, Adam R.
Abstract: Objective: This study examined longitudinal associations between performance on the Rey–Osterrieth Complex Figure–Developmental Scoring System (ROCF-DSS) at 8 years of age and academic outcomes at 16 years of age in 133 children with dextro-transposition of the great arteries (d-TGA). Method: The ROCF-DSS was administered at the age of 8 and the Wechsler Individual Achievement Test, First and Second Edition (WIAT/WIAT-II) at the ages of 8 and 16, respectively. ROCF-DSS protocols were classified by Organization (Organized/Disorganized) and Style (Part-oriented/Holistic). Two-way univariate (ROCF-DSS Organization × Style) ANCOVAs were computed with 16-year academic outcomes as the dependent variables and socioeconomic status (SES) as the covariate. Results: The Organization × Style interaction was not statistically significant. However, ROCF-DSS Organization at 8 years was significantly associated with Reading, Math, Associative, and Assembled academic skills at 16 years, with better organization predicting better academic performance. Conclusions: Performance on the ROCF-DSS, a complex visual-spatial problem-solving task, in children with d-TGA can forecast academic performance in both reading and mathematics nearly a decade later. These findings may have implications for identifying risk in children with other medical and neurodevelopmental disorders affecting brain development.